Adenoviral Vector Vaccination Induces a Conserved Program of CD8(+) T Cell Memory Differentiation in Mouse and Man - Bolinger, Beatrice (Cell Rep, 2015)
Following exposure to vaccines, antigen-specific CD8(+) T cell responses develop as long-term memory pools. Vaccine strategies based on adenoviral vectors, e.g., those developed for HCV, are able to induce and sustain substantial CD8(+) T cell populations. How such populations evolve following vaccination remains to be defined at a transcriptional level. We addressed the transcriptional regulation of divergent CD8(+) T cell memory pools induced by an adenovector encoding a model antigen (beta-galactosidase). We observe transcriptional profiles that mimic those following infection with persistent pathogens, murine and human cytomegalovirus (CMV). Key transcriptional hallmarks include upregulation of homing receptors and anti-apoptotic pathways, driven by conserved networks of transcription factors, including T-bet. In humans, an adenovirus vaccine induced similar CMV-like phenotypes and transcription factor regulation. These data clarify the core features of CD8(+) T cell memory following vaccination with adenovectors and indicate a conserved pathway for memory development shared with persistent herpesviruses.